High energy level diet improves the growth performance and rumen fermentation of yaks in cold weather - Zhu, Yanbin; Sun, Guangming; Luosang-dunzhu,; Li, Xin; Luosang-zhaxi,; Suolang-zhaxi,; Suolang,; Ciyang,; Cidan-yangji,; Basang-wangdui,; Pan, Feng; Peng, Quanhui (Frontiers in Veterinary Science, 2023)
To date, no research has been done on energy requirements for yaks in Tibetan cold weather. The findings of the current study provide proper energy requirements for yaks would facilitate scientific feeding of fattening yaks in cold weather. The metabolomics and 16s rRNA sequencing technologies were used to explore the underlying mechanism that affects the growth performance of yaks fed with different energy levels of diet in cold weather. Three groups of yaks (141.7 ± 3.34 kg) were fed with diets containing metabolizable energy 7.20, 7.89, and 8.58 MJ/kg DM (dry matter) and named the low-, medium-, and high-energy groups, respectively. The results showed that the average daily feed intake of the high-energy group was higher than that of the low-energy group (p = 0.006). Plasma aspartate aminotransferase (p = 0.004), alanine aminotransferase (p < 0.001), and interferon-γ (p < 0.001) in the high-energy group were lower than in the low-energy group. In contrast, superoxide dismutase (p < 0.001), immunoglobulin G (p < 0.001), and interleukin 2 (p = 0.002) were higher than the low-energy group. The rumen microbial protein (p = 0.025), total volatile fatty acids (p = 0.029), and neutral detergent fiber digestibility (p = 0.050) in the high-energy group were higher than in the low-energy group, whereas the acetate: propionate ratio (p = 0.001) and ammonium nitrogen (p = 0.001) were lower than in the low-energy group. The plasma metabolomics results displayed that yaks fed with a high-energy diet augmented the metabolism of arginine, proline, purine, taste transduction, pyrimidine, and glutathione pathways. The relative abundance of Methanobrevibacter in the high-energy group was lower (p < 0.001), whereas the relative abundance of Methanosphaera (p < 0.001) was higher than in the low-energy group. The results of the current study suggest that a high-energy diet in growing yaks during the cold season can improve growth performance, rumen microbial protein synthesis, antioxidants, and immunity.